STRES MAHASISWA PROGRAM STUDI SARJANA KEPERAWATAN DALAM PENYUSUNAN SKRIPSI DIMASA PANDEMI COVID-19 PADA TAHUN KE 2 DI UNIVERSITAS CENDERAWASIH - Diyah Astuti Nurfa’izah; Fransisca B. Baticaca; Nur Azizah (Universitas Pahlawan Tuanku Tambusai, 2022)
Covid-19 is an infectious disease that infects the lungs caused by the Corona virus. Incidence as of May 18, 2021 in Indonesia was 1,744,045, in Papua there were 1,606,611 cases. One of the impacts of Covid-19 on the education sector, one of which is student stress on thesis preparation. The purpose of this study was to identify a description of the stress level of nursing students in the preparation of theses during the Covid-19 pandemic, a type of quantitative descriptive research using a cross sectional study design. The population in this study were 73 final students of PSIK UNCEN, with a total sample of 61 students. This study used univariate analysis. Student stress levels were measured using a questionnaire. The results of the study using a univariate analysis test obtained the characteristics of the majority of students aged 17-25 years (52.5%), women (83.6%), non-Papuan ethnic groups (60.7%), 2019 class year (59.0%). The stress level of students showed light stress as much as 3.3%, moderate stress 70.5%, and severe stress 26.2%. The majority of students experienced moderate physical stress (40.8%), severe psychological stress (69.4%), and mild behavioral stress (92.6%). Overall the level of stress experienced by students is at a moderate level, it is expected that students can prepare themselves in working on and compiling theses diligently, multiply reading literature, be able to manage time well so that theses can be completed on time. Keywords : Stress level, final year students, thesis, Covid-19 pandemic